Desenvolvimento de revestimento comestível incorporado com própolis para uso na conservação de queijo de coalho - Silva, Adriana dos Santos (2018)
Curd cheese is a typical product of the Northeast region, produced mainly in artisanal dairies and marketed in open markets, generally deficient in sanitary quality. The objective of this study was the development of an edible coating based on gum arabic and the incorporation of brown propolis from the State of Sergipe, with the purpose of improving the hygienic sanitary quality and useful life of rennet cheese. Physical and chemical characterization analyzes (color analysis, phytochemical screening, phenolic compounds and flavonoids and high performance liquid chromatography) and microbiological analysis (antimicrobial activity of paper disc diffusion and minimal inhibitory concentration by microdilution in broth) were performed. propolis. Coated and coated cheese was elaborated, evaluating the effectiveness of the coating by means of the challenge test technique, its sensorial acceptability and physicochemical characteristics were also evaluated. The results of characterization of propolis used in this research point to a product with high content of flavonoids (> 3.7%) and high sequestering ability of the DPPH radical (97% inhibition), phytochemical screening and chromatographic profile of brown propolis detected phenolic compounds. Also found as well as excellent results of antimicrobial activity against staphylococcus aureus microorganism with inhibition halos up to 27 mm. Microdilution tests in broth showed that the crude extract of propolis presented inhibition power against the bacteria Staphylococcus aureus and Escherichia coli in all the tested concentrations, being the concentration 32 μg / mL, considered as the lowest concentration not only able to inhibit growth , as well as killing bacteria. The challenge test proved the effectiveness of the propolis-coated coating with Sthapylococcus aureus counts in the constant coated cheese, indicating a bacteriostatic action, the opposite was observed in the control cheese, where there was an expressive growth over the 12 days of experiment, with final log 4.0 log cycles longer than the coated cheese sample. The sensory results in relation to the overall assessment, the highest frequency of grades was attributed to grade 8, equivalent to "I liked it a lot". This frequency of notes was maintained during the three cycles of analysis, the subjective analysis of the coating showed a deficiency in homogeneity during the whole evaluation time, this deficiency could be related to the fact that the coating consists of water, and propolis as it is known, has little solubility in water. The physico-chemical parameters of the cheese resemble results reported in the literature.